Tolerance and adaptation to virtual classes due to the pandemic among university adolescents - Cayllahua, Mirian Carrillo; Flores Marín, Guido; Nieva Villegas, Lilia; Gómez-Gonzales, Walter; Zapana-Tito, Maria (International Journal of Public Health Science (IJPHS), 2024)
After the pandemic, the Ministry of Education proposed the teaching of virtual classes, a measure that generated adaptation processes. The present research aimed to determine the relationship between tolerance to frustration and adaptation to virtual classes due to the pandemic in adolescents from a public and private university. A study was carried Prospective cross-sectional correlational study, the sample made up of 86 students from a private and public university, the survey and instrument technique were used, a Likert scale questionnaire applied via Google Docs, applied to students who have developed face-to-face classes and later they have held virtual classes. The tolerance to frustration in adolescents of the Private University of Huancayo Franklin Roosevelt and the National University of Huancavelica is medium and the adaptation to virtual classes is in the process of adaptation. There is a direct average correlation between tolerance to frustration and adaptation to virtual classes in adolescents from a public and private university in a pandemic; with a Spearman's Rho value of 0.634 and a p. bilateral significance value of 0.000. The Peruvian educational system was not yet prepared for virtual education, finding many deficiencies. We recommend carrying out multicenter studies, which allow the outcomes of this change in educational modality to be compared in various regions.